Solar Cells: An Aromatic Diamine Molecule as the A‐Site Solute for Highly Durable and Efficient Perovskite Solar Cells (Small Methods 1/2019). Issue 1 (7th January 2019) - Kim, Jinhyun; Hwang, Taehyun; Lee, Byungho; Lee, Sangheon; Park, Kimin; Park, Helen Hejin; Park, Byungwoo
Abstract : In article1800361, Byungwoo Park and co‐workers present the role of imidazole as a cation solute for organometal‐halide perovskites. Imidazole is structured with the aromatic and diamine framework, allowing significant improvements on the device performance and stability. Considering the intense attention on stability problems in perovskites, degradation under various conditions are examined to reveal the superior role of imidazole.